2003
DOI: 10.1203/01.pdr.0000069702.25801.d1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Histologic Chorioamnionitis and Early Inflammatory Variables in Blood, Tracheal Aspirates, and Endotracheal Colonization in Preterm Infants

Abstract: Histologic results of the placenta are usually not available within the first days of life. We identified inflammatory variables in tracheal aspirates and blood that were associated with histologic chorioamnionitis (HC). A derivation cohort consisted of 62 neonates and a validation cohort of 57 neonates with a gestational age Ͻ 31 wk and ventilated on d 1. Tracheal aspirates were taken on d 1 and on d 3, if the patient was still ventilated. HC was diagnosed by light microscopy. Logistic regression was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 25 publications
4
50
3
Order By: Relevance
“…Significantly higher levels of TNF-␣ and IL-8 were found in the tracheal aspirates of this group, suggesting increased severity of inflammation in this group. This extends the work of Watterberg et al (21), who showed elevation of IL-1␤ in first-day aspirates from infants who were exposed to intrauterine inflammation, and is also consistent with recently published evidence for IL-8 being an accurate indicator of histologic chorioamnionitis (54). A notable finding in our study is that significantly more infants with chorioamnionitis had lung neutrophils and macrophages expressing NF-B activation in the first week of life.…”
Section: Activated Nf-b In Lung Leukocytessupporting
confidence: 93%
“…Significantly higher levels of TNF-␣ and IL-8 were found in the tracheal aspirates of this group, suggesting increased severity of inflammation in this group. This extends the work of Watterberg et al (21), who showed elevation of IL-1␤ in first-day aspirates from infants who were exposed to intrauterine inflammation, and is also consistent with recently published evidence for IL-8 being an accurate indicator of histologic chorioamnionitis (54). A notable finding in our study is that significantly more infants with chorioamnionitis had lung neutrophils and macrophages expressing NF-B activation in the first week of life.…”
Section: Activated Nf-b In Lung Leukocytessupporting
confidence: 93%
“…Infections and inflammatory processes in both the mother and infant are involved. 20,21 High white counts in our population appear partly explained by maternal infections, as exposure to PROM and chorioamnionitis were common at high total WBC. Low neutrophil counts were very rare in these groups, however.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we demonstrated that TA pro-inflammatory cytokines (e.g. IL-8) measured immediately after birth are significantly increased in infants born from mothers with histologic chorioamnionitis (8).…”
mentioning
confidence: 99%